COMING INTO PUBLIC AREA IN THE SECRET LIVES OF BABA SEGI’S WIVES (2010) BY LOLA SHONEYIN - Wanda Rifani Astuti Nst; Kurnia Ningsih; An Fauzia Rozani Syafei (English Language and Literature, 2018)
This study analyses the issue of coming into public area done by women characters. The aims of this study are to find out how far the two women characters exposed the topic of coming into public area. Fictional devices such as character, plot (conflict), and setting are used to analyse this novel. The analysis is done through text and context-based interpretation. Those elements are analysed based on how characters are going out from domestic area and coming into public area. This study relates to the concept of Marxist-feminis by Holmstorm, C. Delphy, and Booth. The result of this study shows that the women characters success in leaving domestic and coming into public area. Though cultural condition limit them, they struggle to fight to be independent.